Meta-analysis of the prevalence and risk factors associated with bovine neosporosis - Ribeiro, Claudia Mello (2020)
Neospora caninum is one of the main infectious agents that cause reproductive disorders in cattle. However, knowledge about the prevalence and causal factors of bovine neosporosis is needed in order to establish control measures. The purpose of this study was to estimate the pooled prevalence and determine the risk factors of bovine neosporosis using meta-analytic methods. Searches for data on N. caninum seroprevalence and potential risk factors were conducted in the PubMed, LILACS, and SciElo databases. The random effects model was used for the meta-analysis of the included studies. The pooled prevalence of N. caninum in cattle was 24% (95% confidence interval (CI), 19-29) in North and Central America, 24% (95% CI, 20-28) in South America, 18% (95% CI, 14-21) in Asia, 15% (95% CI, 12-18) in Europe, 13% (95% CI, 11-16) in Africa, and 8% (95% CI, 4-14) in Oceania. A significant correlation was found between N. caninum infection and abortion in cows (odds ratio (OR) = 2.66, 95% CI, 1.97-3.59). The following risk factors were signicantly associated with N. caninum seroprevalence: presence of dogs on the farm (OR = 2.84; 95% CI, 1.40-5.80) and the type of cattle production system, with dairy cattle being more susceptible to bovine neosporosis (OR = 1.60; 95% CI, 1.16-2.19) than beef cattle. The adoption of measures to prevent the dissemination of N. caninum in cattle herds is suggested, aiming to reduce the economic losses incurred to the dairy and beef industry.